Ceryl Sdn Bhd “Edible Cutlery" / Nurul Aini Mahmood - Mahmood, Nurul Aini (2020)
Ceryl Sdn Bhd is a company that produces edible cutleries based on green technology which is eco-friendly and nutritious. The company has opened a restaurant that uses a nature concept as the signature for the menu, food presentation and also the interior design of the restaurant. Edible cutleries are used for the whole food presentation to the customers, and also been sold as a restaurant’s merchandise. Ceryl restaurant is the first restaurant in Malaysia that uses edible cutleries for the food presentation and this has become a main attraction to the restaurant itself. Besides, the restaurant also offers merchandise and gifts from these edible cutleries to the customers